The new melatonin derivative: synthesis, characterization, biological properties, and serum determination by HPLC-UV - Mohammed, Srwa Hashim; Karatepe, Mustafa (Springer Heidelberg, 2022)
Melatonin is one of the most significant hormones that have an impact on biological activities. Melatonin is a strange molecule that humans and animals produce in their pineal glands. A small gland found in the center of the brain is known as the pineal body. This research aims to synthesize a new melatonin derivative, assess its biological properties, and design a new HPLC analysis method. In the first stage, benzyl chloride was used to make a novel derivative of this chemical. The melting point was used to check the purity of the produced derivative. The molecular structure of the substance has been confirmed using: Fourier transform infrared (FT-IR), Carbon-13(C13)nuclear magnetic resonance (13C-NMR), Differential scanning calorimetry (DSC) and Proton nuclear magnetic resonance (1H-NMR) spectral studies, and elemental analysis. The antibacterial, antioxidant, and antitumor capabilities of the produced melatonin derivative were then studied using various microbe and antioxidant methods in the second stage. Although the new derivative gave a high antioxidant effect in APTS-99.03% and OH- 99.29% than BHT control, the produced derivative has a relatively negative impact on microorganisms (Staphylococcus aureus 7 mm) and moderate anticancer effect. The method for analyzing the novel derivative in biological samples using HPLC-UV was devised as the final stage using %64 acetonitrile. A PH 4 shows a higher peak and a shorter retention time (3.52 min and absorbance 250 nm).
Keywords: Melatonin; Antioxidant activity; Antimicrobial activity; Cytotoxic activity; HPLC-UV